MOLECULAR DETECTION OF HUMAN RHINOVIRUS IN RESPIRATORY SAMPLES OF SWINE FLU NEGATIVE NORTH INDIAN CHILDREN WITH FLU-LIKE ILLNESS - Gaur, Pooja; Srivastava, Neena; Awasthi, Shally; Katiyar, Ravish; Shrivastava, Nikky N; Singh, Dharam V; Kaistha, Shilpa; Tripathi, Rambha; Misra, Virendra K; Prakash, Vijay; Kapoor, Prerna; Dhole, Tapan N (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Flu-like illness may also be caused by different respiratory viruses other than influenza. Human rhinovirus (HRV) shows almost flu-like symptoms. The purpose of this study is the molecular detection of HRV in throat swab of swine flu negative North Indian children during the years 2012 and 2013. Reverse transcriptase (RT) - polymerase chain reaction (PCR) amplification of 5'non-coding region (NCR) was used for HRV detection followed by cell culture isolation of HRV. Methods: PCR confirmed swine flu negative throat swab samples were collected from the Department of Microbiology, Sanjay Gandhi Post Graduate Institute of Medical Sciences, Lucknow, Uttar Pradesh, India. The RNA isolation of samples was done using the QIAamp Viral RNA Mini Kit (Qiagen), followed by single step RT-PCR amplification (AgPath-ID, Life Technologies). All PCR positive HRV samples were cell cultured in HeLa and HEp-2 cell lines for viral isolation. Â® Results: 135 swine flu negative throat swab samples were examined. Out of which 34 samples (25.2%) were found HRV positive by RT-PCR, while only four samples (11.8%) were culture positive on HeLa cell line. Younger children (0-4 year) were found more susceptible to HRV infection. This study indicated the highest prevalence of HRV (37.0%) during the months (September-October) of the Autumn season in 2012 and 57% in Winter-spring season (February-March) during 2013. Conclusion: HRV may be a cause of flu-like symptoms in swine flu suspected North Indian children with a higher rate during Autumn and Spring season. Molecular detection of HRV using RT-PCR is more sensitive than cell culture assay. Keywords: Human rhinovirus, Swine flu, Influenza-like illness, Lower respiratory tract infections.